Functional Intercellular Transmission of miHTT via Extracellular Vesicles: An In Vitro Proof-of-Mechanism Study - Roberto D. V. S. Morais; Marina Sogorb-González; Citlali Bar; Nikki C. Timmer; M. Leontien Van der Bent; Morgane Wartel; Astrid Vallès (Cells, 2022)
Huntington’s disease (HD) is a fatal neurodegenerative disorder caused by GAG expansion in exon 1 of the huntingtin (HTT) gene. AAV5-miHTT is an adeno-associated virus serotype 5-based vector expressing an engineered HTT-targeting microRNA (miHTT). Preclinical studies demonstrate the brain-wide spread of AAV5-miHTT following a single intrastriatal injection, which is partly mediated by neuronal transport. miHTT has been previously associated with extracellular vesicles (EVs), but whether EVs mediate the intercellular transmission of miHTT remains unknown. A contactless culture system was used to evaluate the transport of miHTT, either from a donor cell line overexpressing miHTT or AAV5-miHTT transduced neurons. Transfer of miHTT to recipient (HEK-293T, HeLa, and HD patient-derived neurons) cells was observed, which significantly reduced HTT mRNA levels. miHTT was present in EV-enriched fractions isolated from culture media. Immunocytochemical and in situ hybridization experiments showed that the signal for miHTT and EV markers co-localized, confirming the transport of miHTT within EVs. In summary, we provide evidence that an engineered miRNA—miHTT—is loaded into EVs, transported across extracellular space, and taken up by neighboring cells, and importantly, that miHTT is active in recipient cells downregulating HTT expression. This represents an additional mechanism contributing to the widespread biodistribution of AAV5-miHTT.